2014
DOI: 10.1186/2036-7902-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound detection of tracheal wall thickening caused by smoke inhalation

Abstract: Smoke inhalation is the leading cause of death due to fires. When a patient presents with smoke inhalation, prompt assessment of the airway and breathing is necessary. Point-of-care ultrasonography (US) is used for the rapid assessment of critically ill or injured patients. We herein present a case report of a 54-year-old male who was transferred to the emergency department with shortness of breath, coughing, carbonaceous sputa, and rhinorrhea after inhaling smoke caused by a fire in his locked bedroom. He had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 13 15 ]. Kameda et al [ 16 ] identified airway edema as hypoechoic thickening of the tracheal wall on airway ultrasound in a patient with inhalational burns. The findings on the sonogram were later confirmed by CT scan, demonstrating good correlation between focused ultrasound and CT Scan.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 15 ]. Kameda et al [ 16 ] identified airway edema as hypoechoic thickening of the tracheal wall on airway ultrasound in a patient with inhalational burns. The findings on the sonogram were later confirmed by CT scan, demonstrating good correlation between focused ultrasound and CT Scan.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Nowadays, interventional radiology is the preferred modality for missed guidewire removal in which snare or basket can be used to retrieve the wire under fluoroscopy guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the known normal values of the tracheal wall, 1.5 ± 0.2 mm in males and 1.2 ± 0.2 mm in females, the possible tracheal thickening can be identified by airway ultrasound. These situations are present in inflammations, infections, tumor infiltration, congenital diseases such as Wegener’s disease, smoke inhalations, or airway burns [ 28 , 29 ].…”
Section: Prediction Of a Difficult Airway And Identification Of Some ...mentioning
confidence: 99%